Prevalence of “weak B” phenotypes and their evaluation and differentiation in healthy blood donor population in Eastern India - Sudipta Sekhar Das; Sourav Mukherjee; Sourav Chowdhury (Asian Journal of Transfusion Science)
BACKGROUND: Examples of group B red cells that react weakly or not at all with anti-B have been described. Subgroups of B such as B3, Bx, Bm, and Bel are rare and are less frequently reported. We studied the frequency of subgroups of B in our healthy blood donor population and serologically characterized and differentiated these subgroups. MATERIALS AND METHODS: The 9-year prospective study included 84,534 healthy blood donors. Initial blood grouping and antibody screening of all donor samples were performed using automated solid-phase assay. Any sample showing blood group discrepancy or weaker agglutination was subjected to further immunohematological investigations. RESULTS: Among 84,534 healthy donors, “B” blood group was found in 29,190 (34.53%). Weak B phenotypes were demonstrated in 9 (0.031%) B donors. Among the 9 weak B phenotypes, B3 was the most common followed by Bm. The frequency of B3, Bm, Bx, and Bel in our blood donor population was found to be 1 in 21,133, 1 in 28,178, 1 in 84,534, and 1 in 84,534, respectively. Red cell agglutination with anti-B and anti-AB varied from Wk+ to 2+ with or without mixed-field agglutination in the B3 and Bx phenotypes. Naturally occurring anti-B of immunoglobulin M type was detected in the Bx donor. Two (22.2%) of the 9 donors were found to be nonsecretor. Adsorption-elution demonstrated “B” antigen specificity in different strengths in Bm, Bx, and Bel phenotypes. CONCLUSION: We conclude that differentiating weak subgroups of “B” by serological assays is possible to a great extent with technical expertise. Mistyping weak subgroups of B as “O” group may lead to reporting errors and wrong blood transfusion. Therefore, blood centers in developing countries including India should establish simple techniques to detect and differentiate weak subgroups and develop procedures to ensure safe blood transfusion and transplantation.